Improper financial planning affects the execution of the development plan in the territorial entities (2019)
The development of the territorial entities is generated from a proper planning of policies, programs and projects, which allow to fulfill an important mission and accumulated this in a constitutional period to achieve the satisfaction of the vision. This margin of planning that in any measure is oriented to the achievement of objectives of well-being in the community, requires the allocation of resources, which allow the development of the planned, from the Municipalities, promoting the success of a municipal administration, since the measure is generated through the monitoring of indicators.